Morphosyntactic sources for nominal synthetic compounds in English and Greek - Gianina Iordăchioaia; Artemis Alexiadou; Andreas Pairamidis (Zeitschrift für Wortbildung)
We analyze English and Greek nominal synthetic compounds like truck driver and truck driving from a syntactic perspective couched within Distributed Morphology. We derive the main differences between the two languages from the different morphosyntactic status of the non-head nouns, which are roots in Greek but categorized words in English.